(untitled) (Research, Society and Development, 2021)
In recent years, mental disorders have affected the population on a large scale, becoming one of the most talked about issues today, which are characterized by a group of brain disorders that trigger symptoms mainly involving emotion, cognitive function and the ability to control behavior complexes, which often follow the chronic path, among these psychopathologies are depressive disorders that have affected the population in a frightening way. Depression is considered a psychopathology in the adult stage only, and it has been showing a high incidence among adolescents, ranging from 3.3% to 12.4%, with a predominance in females. Thus, the research aimed to identify the main triggering factors for depression among adolescents found in the studies. An integrative review of previous studies, complete and available in scientific databases that had been published between 2010 and 2020, was carried out. After exploratory reading, a total of 11 files were selected. The main triggering factors among adolescents highlighted were: family relationships (conflicts and disruption); family background, social vulnerability, gender and age; gender and age; psychoaffective and psychosocial aspects. Based on the researches carried out, it was possible to show that depression among adolescents is multifactorial, as well as in adults, that is, several situations corroborate its emergence, but most studies have pointed out that the main factor is the family environment, the way in which these teenagers are raised, educated and the bond they have with their parents.